Gastric dysplasia arising from a submucosal heterotopic gastric gland - Mayu Kobayashi; Yasuhiko Hamada; Miki Usui; Hayato Nakagawa (JGH Open)
Abstract A submucosal heterotopic gastric gland (SHGG) is characterized by benign ectopic gastric tissue within the submucosa. Neoplasms arising from SHGGs are rare, and their definitive diagnosis via endoscopic biopsy is often challenging. We report the case of a 74‐year‐old man undergoing screening esophagogastroduodenoscopy, which revealed a subepithelial lesion with a central orifice in the upper body of the stomach. Endoscopic submucosal dissection (ESD) was performed because the endoscopic biopsy revealed a suspected pyloric gland adenoma. Pathological examination of the resected specimen confirmed SHGG with focal dysplasia. The patient recovered uneventfully and remained free of recurrence over a 5‐year follow‐up period. This case highlights the utility of ESD in both the treatment and accurate pathological diagnosis of neoplasms arising from SHGGs.